CO2‑Assisted Water-Washing Process of Municipal Solid Waste Incineration Fly Ash for Chloride Removal - Zuo, Wu; Zhao, Runbo; Dong, Guanghui; Ma, Guilin; Zhou, Haiyun; Song, Tao; Tu, Yong; Xie, Hao; Wang, Xinye (Energy & fuels, 2022)
Water washing can remove chlorides from municipal solid waste incineration fly ash but with high consumptions of energy and reagents for the following wastewater treatment. In this study, a novel method named delayed bubbling washing (water washing first and then CO2 bubbling washing) was proposed to promote the chlorine dissolution. The mechanisms were considered as the less shell formed outside ash particles and the reaction between CaClOH and H2CO3 during washing. However, for single-stage washing, the incomplete dehydration of washed ash greatly weakened the chloride removal effect. Three-stage countercurrent washing addressed this issue well with the best bubbling position in the first stage. Through the combination of delayed bubbling washing and three-stage countercurrent washing, the chlorine content in the product was lowered to 0.85% at a liquid–solid ratio of 2.5 mL/g, the cost of wastewater treatment was reduced by 23%, the byproduct of NaCl was reduced by 14.5%, and the CO2 emission was reduced by 23 kg/ton of ash.